New Directions for Historic Conservation: A Methodology, with Special Reference to Kingston - Spragge, Godfrey (Urban History Review / Revue d'histoire urbaine, 1987)
Small outlying hamlets develop around major centres, which are later swallowed up in urban expansion. These hamlets were once thriving communities which have a social history, and which have left us a physical heritage. Few buildings of major architectural significance were built in these hamlets, and the people who lived there were often not those written about in histories. But when the social history is combined with the physical evidence of the hamlets there is in some cases a basis for preserving what remains of them. This article develops a planning methodology, noting historical resources, which might lead to the preservation of buildings which were part of these hamlets. The article is illustrated with examples near the old Town of Kingston in Upper Canada.